2004
DOI: 10.1172/jci19418
|View full text |Cite
|
Sign up to set email alerts
|

High vaccination efficiency of low-affinity epitopes in antitumor immunotherapy

Abstract: Most of the human tumor-associated antigens (TAAs) characterized thus far are derived from nonmutated "self"-proteins. Numerous strategies have been developed to break tolerance to TAAs, combining various forms of antigens with different vectors and adjuvants. However, no study has yet determined how to select epitopes within a given TAA to induce the highest antitumor effector response. We addressed this question by evaluating in HLA-A*0201-transgenic HHD mice the antitumor vaccination efficacy of high-and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…In an earlier peptide immunization study, 48 self-antigens showed markedly lower immunogenicity in HHD mice despite forming stable MHC complexes. In contrast, 3/4 self-antigen peptides in our study generated significant CMI responses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In an earlier peptide immunization study, 48 self-antigens showed markedly lower immunogenicity in HHD mice despite forming stable MHC complexes. In contrast, 3/4 self-antigen peptides in our study generated significant CMI responses.…”
Section: Discussionmentioning
confidence: 91%
“…This increase in immunogenicity may be offset further by a potential decrease in CTL avidity 47 . Nonetheless, the use of analogs may be warranted in cases in which the analog is significantly more immunogenic than the native peptide 45 , 48 . For example, analogs of CEA.310 and TERT.540(10) (Table 1) and the analogs of CEA.411 and CEA.589 that we have previously described 49 are immunogenic while the native peptides are not.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations consisted of aqueous solutions of hTERT peptides I540 (ILAKFLHWL) (42), 572Y (YLFFYRKSU) (43), 988Y (YLQVNSLQTV) (43), Sur1M2 (LMLGEFLKL) (44), and N495 (NLVPMVATV) from CMV pp65 (45) (each peptide >92% pure and Good Manufacturing Practice–grade; Merck Biosciences AG) emulsified in the adjuvant Montanide ISA 51 VG (Seppic) and delivered subcutaneously in the thighs. Sargramostim (clinical-grade granulocyte-macrophage colony-stimulating factor; Berlex Laboratories) was given subcutaneously at the two injection sites (70 μg per site) with each peptide vaccination.…”
Section: Methodsmentioning
confidence: 99%
“…1A, the hTERT immunogen was developed with several modifications, including codon/RNA optimization and the addition of a highly efficient leader sequence, to enhance the expression and immunogenicity of phTERT. Two mutations (R589Y and D1005Y) were incorporated into the hTERT sequence to assist in breaking tolerance (41). The modified gene was subcloned into pGX0001 and named as phTERT for further study (Fig.…”
Section: Resultsmentioning
confidence: 99%